CAUSES OF ATMOSPHERIC AIR POLLUTION AND POSSIBILITIES FOR ITS PROTECTION (Archive of Conferences, 2021)
It is known that today, due to the rapid development of technological processes, the demand for fuel resources in energy and other industries is growing.